ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI TEOREMA PYTHAGORAS DITINJAU DARI PERBEDAAN GENDER - Imelza Patri; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze students' difficulties in solving problems on the Pythagorean Theorem material in terms of gender differences. This study used a qualitative descriptive method conducted at SMP Negeri 2 Pasir Penyu in the 2025–2026 academic year. The research sample consisted of 29 students of class VIII.2 selected using a purposive sampling technique. Data collection was carried out through a descriptive test consisting of four questions related to the Pythagorean Theorem material. The results showed that male and female students both experienced difficulties in understanding problems, determining formulas, performing calculations, and drawing conclusions. Male students tended to experience difficulties in technical aspects, such as arithmetic operations, calculation accuracy, and solution procedures, while female students experienced more difficulties in non-technical aspects, such as explaining concepts, completing information, and writing final conclusions. This study has a positive impact as evaluation material for teachers in designing more effective mathematics learning according to student characteristics, thereby helping to minimize learning difficulties in the Pythagorean Theorem material.Keywords: Learning Difficulties, Pythagorean Theorem, Gender, Mathematics